An Analysis of Illocutionary Act in “Ratatouille” A Movie by Brad Brid - Bela Antalia Putri Asykin; Suyadi Suyadi; Efa Silfia (Universitas Batanghari Jambi, 2021)
This study aimed to find out the type of illocutionary acts that is contained the utterance of the main character and to determine the most dominant illocutionary act that is used by the main character in the movie. This research use applies qualitative method. As the result there are 48 utterances that contain illocutionary act found in Ratatouille movie. The researcher found 4 classifications of illocutionary act by using Yule’s classification. The fourth types are; directives found 20 utterances, expressive found 11 utterances, representatives found 10 utterances and commissive found 6 utterances. The researcher not found the type of illocutionary act of declaration. The most dominant illocutionary act is directives.Key Words: Speech acts, Illocutionary acts, Ratatouille Movie